(untitled) (Global Journal of Medical Research, 2013)
This study was designed to assess short-term therapeutic effectiveness and psychological adverse effects of combination of pegylated interferon α-2a and ribavirin in Iraqi chronic hepatitis C patients. For this purpose fifty newly diagnosed chronic hepatitis C patients divided into three groups A, B and C, treated with equal doses of pegylated interferon α-2a (180 μg/week) and different doses of ribavirin (1200, 1000 and 800 mg/day respectively) and followed up for 12 weeks of starting treatment (prospective groups). Twenty healthy subjects were selected to be a normal group for the purpose of comparison. The results at week 12 (the time of achieving EVR) showed 100% complete EVR (cEVR) in group A, 4.4% cEVR and 5.6% null response in group B, 88.9% cEVR and 11.1% partial response in group C.